Biomass Decomposition and Phosphorus Release from Residues of Cover Crops under No‐Tillage. (1st January 2017) - Varela, María Florencia; Barraco, Mirian; Gili, Adriana; Taboada, Miguel Angel; Rubio, Gerardo
Abstract : Residue decomposition and P release was studied under no tillage field conditions. Cover crop residues releases significant quantities of P for the subsequent cash crop. Phosphorus release from residues is affected by precipitation regime and residue quality. A positive tradeoff was observed between crop residue P dynamics and soil coverage. Under no‐tillage field conditions, cover crop (CC) residues remain on the soil surface and decompose at a slow rate. We used three CC species (oat, A vena sativa L.; rye, Secale cereale L.; and ryegrass, Lolium multiflorum L.) to evaluate the residue biomass decomposition and P pools release–total phosphorus (Pt), inorganic phosphorus (Pi), and organic phosphorus (Po)–under no‐tillage field conditions. The dynamics of biomass and P in CC residues was evaluated through the litterbag method during two annual periods in a long‐term field experiment. Exponential decay models were fitted to each variable. Biomass decomposition and P release followed asymptotic decay models for the less labile residues (oat and rye) and single exponential decay models for the more labile ryegrass residues. Biomass and Pt showed rather equivalent dynamics, but Pi release was faster (Pi rates were three times higher and Pi plateaus were two to four times lower than biomass values). The release of Pt from CC residues reached agronomically significant quantities (2–16 kg ha −1 ) during the cash crop growing season and most of this Pt was released as Pi (53–100%). A positive tradeoff was observed between the release of Pi, potentially available for subsequent crop, and the residue biomass remaining over the soil. This means that Pi was released from residues, but enough biomass remained on the soil surface for erosion control. These results can be incorporated into predictive models on the contribution of CC residues to soil coverage and P nutrition of subsequent crops.